The Impact of Green Skills Training and Cross-Sector Collaboration on Workforce Competence through Digital Adaptability in the Central Java Industrial Area - Elshifa, Aria; Novitasari, Salwa Aulia; Pahrijal, Rival (West Science Social and Humanities Studies, 2025)
This study investigates the influence of green skills training and inter-sector collaboration on workforce competency, with digital adaptation acting as a mediating variable within the Central Java industrial area. Using a quantitative design, data were obtained from 150 employees across manufacturing, food processing, textile, and electronics sectors, and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings reveal that both green skills training and inter-sector collaboration have significant positive effects on workforce competency, directly and indirectly through digital adaptation. Green skills training improves employees’ technical and environmental literacy, while collaboration among government, industry, and academia enhances knowledge sharing and capacity building. Digital adaptation functions as a pivotal intermediary that strengthens the impact of sustainability-oriented learning and collaboration on competency outcomes. The model demonstrates high explanatory power (R² = 0.69) and predictive relevance (Q² = 0.42). These results emphasize that integrating environmental and digital competencies is vital to shaping a future-ready workforce capable of supporting sustainable industrial transformation. The study advances Human Capital Theory and Dynamic Capability Theory by evidencing that workforce competency evolves through continuous green training, collaborative innovation, and adaptive digitalization. It further suggests that Indonesian policymakers and industry leaders should promote cross-sector programs that align green upskilling with digital readiness to enhance industrial competitiveness in the era of Industry 4.0 and sustainable development.